Implementing Confidentiality Principles in Sharia Economic Dispute Resolution Through Online Dispute Resolution in Indonesia - Fidhayanti, Dwi; Mohd Noh, Mohd Shahid; Ramadhita, Ramadhita; Setyobudi, Teguh; Dwi Septyanto, Mochamad Fikry (Al-Risalah, 2025)
The resolution of Sharia economic disputes through Online Dispute Resolution (ODR) in Indonesia has been growing in parallel with advancements in digital technology. In this context, the principle of confidentiality has become a crucial aspect to protect the privacy and security of the disputing parties' information. This research aims to analyze the implementation of the principle of confidentiality in ODR within arbitration institutions in Indonesia and identify the challenges and solutions related to data protection. The methodology employed is a sociological-juridical approach, utilizing primary data collected through interviews, focus group discussions (FGD), and documentation, alongside secondary data from relevant journals and regulations. The findings indicate that, while institutions such as Basyarnas and BANI have implemented various protocols to uphold confidentiality, including the use of secure digital platforms and strict regulations on data access, significant challenges remain, notably the potential for data breaches due to cyberattacks or technical negligence. Furthermore, inconsistencies in laws and legal interpretations have created legal uncertainty, which in turn impacts privacy protection. The contribution of this research is to provide recommendations for strengthening digital security standards, consistent policies, and raising awareness of the importance of confidentiality in ODR, thereby creating legal certainty and enhancing trust in the online resolution of Sharia economic disputes.